Effect of different storage conditions on the virulence of Helicoverpa armigera nucleopolyhedrovirus (HaNPV) - Kumar, P. Lava; Sireesha, K.; Ranga Rao, G.V.; Kumar, C.S.; Arjuna Rao, P. (2010)
Studies on the effect of different storage conditions on the virulence of NPV revealed that samples stored in earthen pot and at room temperature maintained efficacy up to four months and after that virulence started decreasing. This decreased efficacy of samples stored under room temperature may be due to increased bacterial activity. When the NPV samples were tested for the bacterial load, it was 3.47 times more in the samples stored at room temperatures after six months of storage.